Vibration analysis and structural identification of a curved multi-span viaduct. (March 2015) - Benedettini, Francesco; Dilena, Michele; Morassi, Antonino
Abstract: This work continues a line of research aimed at the development of a dynamically based monitoring program of bridges in the area of Friuli Venezia Giulia, Italy. The main infrastructure of the survey program is the curved 15-span post-tensioned concrete viaduct considered in this paper. The viaduct consists of three continuous girders separated by expansion joints and supported on piers by means of elastomeric seismic isolators. Output-only vibration tests under traffic loads were carried out to extract the dynamic parameters of the first vibration modes of the structure. The experimental characteristics were compared with those predicted by a preliminary finite-element model. The properties of vibration modes with prevailing amplitudes along the radial and circumferential direction of the viaduct were described with poor precision. This disagreement required the calibration of the finite-element model through a tuning procedure based on modal data. In particular, the experience has shown that the dynamic behavior of the viaduct is strongly influenced by the mechanical properties of the bearing devices supporting the deck superstructures. The calibrated finite-element model can be used as a baseline model for future monitoring and condition assessment programs on this typology of infrastructures. Abstract : Highlights: We interpret output-only vibration tests on a curved 15-span concrete viaduct. We give a justification of the poor precision of a preliminary FE model. The analysis is based on a tuning procedure of the FE model from dynamic data. The research allows us to highlight typical properties of this class of bridges.